Radio i oralność – z perspektywy językoznawczej - Kita, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
Radio as a sound medium, as elaborated in the typical definition of it, constitutes an integral component of the human audiosphere. Human culture is, at source, oral in nature. Orality, a huge category that operates outside of individual academic disciplines, is that which links in a synergy the human being, culture and language, as well as linguistic communication. The author, starting from these ruminations, shows how the theory of orality created by Walter J. Ong may constitute a stable instrument for the description of language and linguistic-communicative behaviours on radio, and enable us to interpret numerous phenomena of radio discourse.